1983
DOI: 10.2466/pr0.1983.53.3f.1083
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Assessment of Locus of Control and Obesity

Abstract: Previous research examining locus of control among the obese has been contradictory. Previous research has examined locus of control among the obese using Rotter's I-E test, a unidimensional questionnaire. The present study examined locus of control among 20 obese and 42 average weight research participants using the Reid-Ware three-factor I-E test. The obese group scored more external on the Self-control scale and on the Social System Control scale. The obese were not more external on the Fatalism scale. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Obese children and adolescents are under the risk factor of short and long‐term medical problems such as gallstones, orthepedic abnormalities, asthma, and increased intracranial pressure, cardiovascular disease, diabetes 2 and adult obesity 12,14,18–22 …”
mentioning
confidence: 99%
“…Obese children and adolescents are under the risk factor of short and long‐term medical problems such as gallstones, orthepedic abnormalities, asthma, and increased intracranial pressure, cardiovascular disease, diabetes 2 and adult obesity 12,14,18–22 …”
mentioning
confidence: 99%
“…Earlier studies of pain-free subjects have shown no significant gender differences (e.g. Kerr, 1986;Thomason, 1983), whereas Tait and coworkers (1982) concided that women may be more prone to helplessness when faced with chronic back pain. Our results give further confirmation of this conclusion by correcting the results for age, characteristics of low back pain and psychological distress.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are similar to those found by others. Thomason (1983) suggests that obese individuals exhibit externality only in certain and limited endeavors. In other words, in Thomason's opinion externality is not a generalized trait that covers everything an individual does.…”
Section: Discussionmentioning
confidence: 99%